Aggrey Klaaste : the relentless community-builder - Mbonambi, Phakama (Rhodes University, Faculty of Humanities, Institute for the Study of English in Africa, 2014)
This thesis looks at the life and times of Aggrey Klaaste, the larger-than-life late editor of Sowetan who shot to fame by championing a novel idea of nation building. His initiative started in 1988 as flames of violence engulfed South Africa and it seemed as if an apocalypse was on the cards. Sickened by what the frustrated black community was doing to itself, for example the use of the dreadful practice of necklacing against the so-called collaborators, he called for moral regeneration. He wanted his compatriots to look into the future and take their destiny in their own hands. Through nation building he tirelessly launched into crusading journalism that sought to heal the scars of the black community after decades of apartheid. It was grassroots community building. He rewarded ordinary men and women who made a difference in their communities. He actively sought peace to end the violence of the 1980s and 1990s. He spoke his mind without wearing any ideological blinkers, even as some thought his initiative would disturb the march to freedom. He was the ultimate newspaperman. This thesis argues that by calling for reconciliation and rebuilding of battered black communities even before freedom came, Klaaste was ahead of his time and even predated Nelson Mandela. Klaaste preferred to do what was right and not be shackled to any ideology. In doing so, he angered many people who felt his thinking was derailing the struggle for freedom. But Klaaste stressed that nation building was ideologically neutral and was meant for everyone. By contradicting prevailing political orthodoxy, he very likely risked his own life. But, like a true leader, he stuck to his convictions. Klaaste was exemplary in calling for reconciliation and building when others called for breaking. Ten years after he died, as the country still grapples with issues he raised in his popular weekly column On The Line, it is worth appraising his thinking and actions. The thesis also looks at the environment that influenced his thinking. His life is interwoven with South African history. That he began his adult life shakily, spending his days in a drunken stupor at Johannesburg shebeens to being awarded the Order for Meritorious Service for his outstanding community work, makes him an interesting subject to look at. It's a story of a man who vanquished his demons and, through his compassionate community engagement, became an asset to the country. It's a story of redemption. As his private life attests, he was man with flaws "“ like anyone else. But Aggrey Klaaste strived to do what was right for his community at all times. He was a restless community builder.
Keywords: Klaaste, Aggrey; Sowetan (Johannesburg, -- South Africa); Newspaper editors -- South Africa -- Biography; Nation-building -- South Africa; South Africa -- Politics and government -- 20th century